Minimal Crossover between Mutations Associated with Omicron Variant of SARS-CoV-2 and CD8 + T-Cell Epitopes Identified in COVID-19 Convalescent Individuals - Redd, Andrew D.; Nardin, Alessandra; Kared, Hassen; Bloch, Evan M.; Abel, Brian; Pekosz, Andrew; Laeyendecker, Oliver; Fehlings, Michael; Quinn, Thomas C.; Tobian, Aaron A. R. (mBio, 2022)
The newly identified Omicron variant of concern contains more mutations than any of the previous variants described to date. In addition, many of the mutations associated with the Omicron variant are found in areas that are likely bound by neutralizing antibodies, suggesting that the first line of immunological defense against COVID-19 is compromised. There is a growing concern that ongoing evolution of SARS-CoV-2 could lead to variants of concern (VOC) that are capable of avoiding some or all of the multifaceted immune response generated by both prior infection or vaccination, with the recently described B.1.1.529 (Omicron) VOC being of particular interest. Peripheral blood mononuclear cell samples from PCR-confirmed, recovered COVID-19 convalescent individuals ( n = 30) infected with SARS-CoV-2 in the United States collected in April and May 2020 who possessed at least one or more of six different HLA haplotypes were selected for examination of their anti-SARS-CoV-2 CD8 + T-cell responses using a multiplexed peptide-major histocompatibility complex tetramer staining approach. This analysis examined if the previously identified viral epitopes targeted by CD8 + T cells in these individuals ( n = 52 distinct epitopes) are mutated in the newly described Omicron VOC ( n = 50 mutations). Within this population, only one low-prevalence epitope from the Spike protein, restricted to two HLA alleles and found in 2/30 (7%) individuals, contained a single amino acid change associated with the Omicron VOC. These data suggest that virtually all individuals with existing anti-SARS-CoV-2 CD8 + T-cell responses should recognize the Omicron VOC and that SARS-CoV-2 has not evolved extensive T-cell escape mutations at this time. IMPORTANCE The newly identified Omicron variant of concern contains more mutations than any of the previous variants described to date. In addition, many of the mutations associated with the Omicron variant are found in areas that are likely bound by neutralizing antibodies, suggesting that the first line of immunological defense against COVID-19 is compromised. However, both natural infection and vaccination develop T-cell-based responses in addition to antibodies. This study examined if the parts of the virus, or epitopes, targeted by the CD8 + T-cell response in 30 individuals who recovered from COVID-19 in 2020 were mutated in the Omicron variant. Only one of 52 epitopes identified in this population contained an amino acid that was mutated in Omicron. These data suggest that the T-cell immune response in previously infected, and most likely vaccinated, individuals should still be effective against Omicron.